Samba Ng'oma eight - The drum chime of Mário Sabuneti - Malamusi, Moya Aliya (International Library of African Music, 2017)
The group Samba Ng'oma, whose leader is Mário Sabuneti, about 20 years old, comes from Nnesa village, T.A. Mabuka, Mulanje District, Malawi. He and his two co-performers, Julias Sabuneti, 18, and Samuel Magwela, 17, have created a new type of music which they call samba ng'oma featuring a set of eight tuned drums to be performed by one person (Mario Sabuneti). Although the group originated in Mulanje District, at the time of my research they were living in the area of the city of Blantyre in southern Malawi, where they had rented a house; the exact place they preferred to stay was in a small township east of Limbe, called Bangwe.
Keywords: African Music